Function of the General Election Supervisory Body in Enforcement General Election Law in the 2024 DPR, DPD and DPRD Member Elections for West Nusa Tenggara Province - Dilman, Dilman (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study uses descriptive qualitative method with institutional and management approaches. The variables were studied are patterns of relationship and communication, as well as accommodation and governance functions. The data were obtained from interviews informants and secondary data on laws, regulations, and reading materials that have relevance to the problems examined. The results showed that Bawaslu role in the handling of violations in the general elections of DPR, DPD and DPRD members year 2024 in Nusa Tenggara Barat province is still less than optimal, it is caused by several factors: first, the lack of capacity of human resources (HR); weak human resource capacity of election supervisors at the district / city and election supervisory ranks below to understand and carry out their duties and functions. This condition occurs because of the nature of institutional panwaskab / town which is adhoc, adhoc election recruitment pattern is still not good, and the low budgetary allocation surveillance in the area. Second, regulatory factors, there are a number of provisions that restrict Bawaslu in maximizing its role, such as: short handling time violation, Bawaslu is not authorized to forcedly call in the clarification process, and the obligation to prepare minimum of two (2) evidence in forwarding the recommendations. While seen from the institutional relations, functions of accommodation, and governance held Bawaslu of Nusa tenggara Barat province has been going well, and be a driving factor for Bawaslu of Nusa Tenggra barat  province in the implementation of institutional management to optimize the role of Bawaslu of Nusa tenggara Barat province in the handling of violations and electoral law enforcement in the election of DPR, DPD and DPRD year 2024.